Republic of Slovenia : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2019)
This Selected Issues paper argues that revenue-neutral tax rebalancing would help Slovenia address long-term fiscal and growth challenges. The present tax-benefit system is supportive of distributional fairness in Slovenia; however, it is argued that tax reform can help bring stronger employment and productivity growth and enhanced resilience to the challenges of population ageing. The paper lays out the case for tax reform in view of long-run fiscal and growth challenges and it also reviews the current tax system and its weaknesses in comparison with international best practices. The paper also sets out tax reform options and uses a model simulation to illustrate the medium- to long-term fiscal and growth impact. The analysis on the tax rebalancing impact suggests that it can permanently and significantly increase potential output in Slovenia. The simulations indicate that a revenue-neutral tax rebalancing has positive fiscal and growth benefits over time.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet